Capacitación en contrataciones públicas y eficiencia operativa en el Hospital Regional de Pucallpa 2024 - Tenazoa Vela, Maritza (2025)
The study was designed to determine the relationship between training in public procurement and operational efficiency at the Pucallpa 2024 Regional Hospital. To do so, a basic, descriptive correlational research was carried out with a non-experimental design, with a sample of 60 people. It was concluded that training in public procurement at the aforementioned hospital is considered regular, reaching only 40% approval. This perception is evident in the responses of the respondents, who stated that the objectives of the training were only explained clearly at the beginning on a few occasions. Likewise, operational efficiency was also rated as regular, with 38% of the participants stating that only occasionally analyses are carried out to identify bottlenecks in clinical and administrative processes. Finally, the correlation test yielded a coefficient of 0.860, indicating a positive and strong relationship between training in public procurement and operational efficiency. This significant correlation was confirmed with a p-value of 0.000, which validates the alternative hypothesis of a relevant link between both variables.